EMPIRIC INDICATORS OF PERFECTIONISM INFLUENCE ON THE PROFESSIONAL IDENTITY OF OFFICERS - Kuzina, Viktoria (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to the study of problem of empiric indicators of perfectionism as a factor of professional identity development of officers of the Armed Forces of Ukraine. As a result of empiric research the groups of officers are set with the different level of display of perfectionism: 1 group with a high level, 2 groups – with middle, 3 groups – with low. Found out uneven correlation of constituents of perfectionism (oriented to itself, oriented on other and socially conditioned), that shows up in different expressiveness of separate components in types after the groups of investigated. To the officers 1 and 2 groups it is more peculiar to produce extraordinarily high demands to itself, however to a 1 group in a greater degree for other it is peculiar to pull out high demands to circumferential, they are inclined to consider requirements which are pulled out to them by colleagues as overpriced and unrealistic. Perfectionism, oriented to itself (from between other scales) most expressive for officers 2 groups which can produce higher requirements to itself, than to surroundings. For officers 3 groups socially conditioned perfectionism appeared most expressive, as a tendency to consider requirements which are pulled out to them by chiefs and colleagues as overpriced. For the officers of a 1 group most expressive is diffuse style of professional identity (making decision in motion, laying on indefinite time) and in a less degree normative style (aspiration to follow traditions, group norms, socially desired variants of decision). For officers 2 groups – informative (aspiration to get maximum information in the situation of present choice, importance of purpose on your own) and normative styles, and for 3 groups is informative style of professional identity in combination with high constancy of lining up a conduct in a professional environment. Discovered cross-correlation copulas show direct dependence between semantic descriptions of perfectionism and indexes of professional claim of officers and stylish features them professional identity.